(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The biological importance of one of the most essential heterocycles, the pyrimidine, is discussed in this paper. The majority of physiologically and medicinally essential substances containing pyrimidine and its derivatives have been covered. The current study focuses on pyrimidine and its numerous derivatives as antimicrobial agents, which is a significant chemical moietys.